MIND MAPPING MATA PELAJARAN MATEMATIKA UNTUK KELAS IX SEMESTER GANJIL - Ni Luh Emi Dayani; Nurhayati Abbas; Yamin Ismail (Universitas Negeri Gorontalo, 2021)
The study s a qualitative descriptive approach, and his research type is the study of library studies. Researchers aim to project sub-sub materials through the mathematical mind mapping of major semester ix classes, researchers are trying to collect data by reading, studying understanding and analyzing books as well as research journals, accessing Internet sites, or documents related to mind mapping. Mind mapping is the most effective and efficient way to input, store and extract data from the brain or into the brain. It works according to the natural workings of our brain, thus optimizing all the human brain's potential and capacity. The manufacturing of the mind mapping process requires that a number of basic characteristics are attained. There is also the basic characteristic; Paper, colour, line, letter, keyword, key image, and structure. Thus basically the mind mapping process is based on the development of the mind mapping process, resulting in a mind mapping that can help teachers and students in the mathematical process during the difficult part of the semester, and can make learning more meaningful and enjoyable because the learning material is visible to the whole so that students can readily understand the material given.